Remote work during the COVID-19 pandemic on the example of the Republic of Kazakhstan: employers’ opinion - G. B. Pestunova; E. A. Vechkinzova (Управление)
The conducted field studies made it possible to determine the degree of COVID-19 pandemic influence on the enterprises’ activities in the East Kazakhstan region, and found out the opinion of employers about the forms of state support for maintaining employment when switching to a remote work format. The researchers faced a number of tasks to determine the degree of COVID-19 pandemic impact on the activities of enterprises in the region. It was necessary to find out how the restrictions on profits were affected and what measures were taken by employers to reduce costs, as well as to identify the degree of remote work impact on productivity. The research is based on the methodology proposed by the International Labor Organization to identify the risks of employers in the context of the COVID-19 pandemic. The proposed questionnaire was adapted to local conditions. The survey was conducted among employers of one of Kazakhstan industrial cities at a time when not all restrictions were lifted, which allowed authors to obtain reliable information. Studies have confirmed the hypothesis that digitalization provides an increase in the efficiency of a modern enterprise and is able to maintain the level of employment under the constraints caused by the COVID-19 pandemic, provided that an environment is created for its application. The risks identified during the survey can be studied and taken into account by public authorities, financial organizations and other stakeholders when planning measures to restore the real sector of the economy from the crisis.